Home-Based Peanut Oral Immunotherapy for Low-Risk Peanut-Allergic Preschoolers During the COVID-19 Pandemic and Beyond - Chua, Gilbert T.; Chan, Edmond S.; Soller, Lianne; Cook, Victoria E.; Vander Leek, Timothy K.; Mak, Raymond (Frontiers in Allergy, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has led to the deprioritization of non-emergency services, such as oral food challenges and the initiation of oral immunotherapy (OIT) for food-allergic children. Recent studies have suggested that home-based peanut OIT could be a safe and effective option for low-risk peanut-allergic children. In the period between September 1, 2020, and January 31, 2021, nine preschoolers with a history of mild allergic reactions to peanut underwent home-based peanut OIT. Eight of them (88.9%) completed the build-up phase at home in 11–28 weeks, tolerating a daily maintenance dose of 320 mg peanut protein. During the build-up, six patients (75.0%) reported urticaria, three (33.3%) reported gastrointestinal tract symptoms, and one (14.3%) reported oral pruritis. None of the patients developed anaphylaxis, required epinephrine, or attended emergency services related to OIT. One or two virtual follow-up visits were completed per patient during the build-up phase. Our case series shows that home-based OIT could be offered to the low-risk preschoolers during the COVID-19 pandemic when non-emergency services are limited and could be considered beyond the pandemic, especially for the families living in the rural or remote areas that may otherwise be unable to access OIT.